Produção rígida, acumulação flexível: comandos globais e processos urbano-regionais na região mínero siderúrgica do Alto Paraopeba, Minas Gerais - Leandro de Aguiar e Souza (2015)
The present thesis is originated from a territorial study about the Region of Alto Paraopeba, located in Minas Gerais State, Brazil, historically linked to the mining and steel circuits of production. From this point were developed discussions in different scales: regional, national and global. Therefore, was comprehended how the great global capital, linked to the mining and steel production, establishes nets of production in the global space. It was found that, despite the peculiarities between companies and its markets, the mining and steel circuits are organized through nets of production relatively similar. These circuits are organized from command centres, strongly articulated with the finance system, that control the production remotely through technological information systems. To reach the territories and produce commodities and spaces in large scale, the command centres need, at different situations, negotiate conditions established by National States. This situation happens because, in global productive circuits, the production of commodities tends to occur in other countries, out of the command centres. It was perceived that, at the context of mining and steel global circuits, the Brazilian State has been acting to viabilize the production of low value commodities, mainly directed to external markets. A large circuit of production and appropriation of surplus value is formed, and the regional scale is the basic source of these values. At this context the Region of Alto Paraopeba has been produced from a great alliance between the industrial capital and the State. Thereby, the fundamental decisions have been made without the participation of the local societies which, in some situations, has articulated its actions to the appropriation of small portions of values produced and, in others, has resisted to the establishment of new cycles of exploration.